هل من علاقة ما بين شرب المتة والداء القرحي الهضمي؟ - دغمـان دعـد (Latakia University Journal -Medical Sciences Series, 2019)
انتشرت في السنوات الأخيرة ظاهرة شرب المتة بشكل واسع في سوريا، والمتة هي شراب ساخن من عائلة Ilex paraguariensis ، يستهلك بشكل واسع في أمريكا اللاتينية وقد دخل بلدنا في العقود الأخيرة، ولا يزال ينقصنا وجود دراسات حول تأثيره على مختلف الأعضاء. شملت هذه الدراسة المستقبلية 236 مريض من مراجعي العيادة الهضمية (out- patient،) قسموا إلى عينتين: العينة (A) وشملت 166 مريض وهم الذين لا يشربون المتة، والعينة (B) وشملت 70 مريضاً وهم من شاربي المتة. بلغت الموجودات التنظيرية الايجابية عند العينة A (44%) بينما كانت بالعينة B (62%), P<0,05)). وشكلت القرحة العفجية النسبة الأكبر من هذه الموجودات وبلغت بالعينة A ( 26 %) بينما بلغت بالعينة B (33 %) . ازدادت نسبة القرحة العفجية عندما تشارك التدخين مع استهلاك المتة ووصلت نسبة القرحة العفجية إلى (42%) في هذة العينة مقابل (26%) للعينة A. ان هذة النتائج تشير بوضوح لوجود دور ما للمتة في إمراضية الداء القرحي خاصة اذا ما ترافقت مع التدخين. Mate drinking phenomena has recently started to spread widely in Syria; it is a hot infusion of the ilex paraguariegensis family. Largely consumed in Latin America, it has entered our country over the past decades, and we still lack studies of its effect on different organs. This prospective study includes 236 patients (outpatients) divided into two groups: A= 166 non-mate–drinker patients, group B=70 mate drinker patients. The incidence of positive endoscopic finding was higher in group B ( 62%) while it was (44%) in group A, (P<0,05). The percentage of duodenal ulcer was (33%) in group B, while it was (26%) in group A, and this percentage increased when mate consumption was associated with smoking, becoming 42% in this group, while it was 26% in group A (p<0,05). These results indicate clearly that there is a relation between mate consumption and peptic ulcer disease, especially when it is associated with smoking.